Kinerja PT Wotraco Bali Raya (Ditinjau dari Balanced Scorecard) - FRESSATRIA, FRESSATRIA; ANTARA, MADE; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.1, No.2, Oktober 2012, 2012)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} ABSTRACT Performance PT Wotraco Bali Raya (In terms of Balanced Scorecard) Balanced scorecard is a management system for companies to invest in the long termin order to achieve certain financial results that enable the development of a business organization rather than simply managing the bottom line to boost short-termresults . The purpose of this study was to determine the performance of PT Wotraco Bali Raya viewed from four perspectives of balanced scorecard namely financial perspective , customer perspective , internal business process perspective , and learning and growth perspective of the year 2009 till 2011.The research was conducted in PT Wotraco Bali Raya which is housed in the 116 Tukad Pakerisan Denpasar . Types of data collected in clude quantitative and qualitative data . Data collection methods used were interviews , observation , and study documentation . The results showed the performance of PT Wotraco Bali Raya from 2009 till 2011 from a financial perspective gained an average of 169.87 % current ratio , debt to total assets ratio of 203.14 %, and the net profit margin of 22.12 %. From the perspective of the customer , the customer growth rate obtained for 2.43% , and the rate of repeat customers and customer satisfaction is not still providea positive perception or satisfied . From the perspective of internal business process efficiency product order transaction completion time obtained an average of 1.29 MCE . From the perspective of learning and growth , the level of productivity of employeesearned an averageof Rp . 1,088,821.18 , the retention rate of employeesearnan average of 3.33% , and the level of employee satisfaction providesa positive perception or satisfied . Based on this research,the authors suggestion is the need for companies rais edfunds , to maintain quality of service to customers, and maintaining the reservation service. Keyword: Perfomance, Companies, Balanced Scorecard